Causal Evidence for Mnemonic Metacognition in Human Precuneus (J Neurosci, 2018)
Metacognition is the capacity to introspectively monitor and control one's own cognitive processes. Previous anatomical and functional neuroimaging findings implicated the important role of the precuneus in metacognition processing, especially during mnemonic tasks. However, the issue of whether this medial parietal cortex is a domain-specific region that supports mnemonic metacognition remains controversial. Here, we focally disrupted this parietal area with repetitive transcranial magnetic stimulation in healthy human participants of both sexes, seeking to ascertain its functional necessity for metacognition in memory versus perceptual decisions. Perturbing precuneal activity selectively impaired metacognitive efficiency of temporal-order memory judgment, but not perceptual discrimination. Moreover, the correlation in individuals' metacognitive efficiency between domains disappeared when the precuneus was perturbed. Together, these findings provide evidence reinforcing the notion that the precuneal region plays an important role in mediating metacognition of episodic memory retrieval. SIGNIFICANCE STATEMENT Theories on the neural basis of metacognition have thus far been largely centered on the role of the prefrontal cortex. Here we refined the theoretical framework through characterizing a unique precuneal involvement in mnemonic metacognition with a noninvasive but inferentially powerful method: transcranial magnetic stimulation. By quantifying metacognitive efficiency across two distinct domains (memory vs perception) that are matched for stimulus characteristics, we reveal an instrumental role of the precuneus in mnemonic metacognition. This causal evidence corroborates ample clinical reports that parietal lobe lesions often produce inaccurate self-reports of confidence in memory recollection and establish the precuneus as a nexus for the introspective ability to evaluate the success of memory judgment in humans.